2023
DOI: 10.3389/fonc.2023.1064343
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of preoperative inflammatory markers in postoperative patients with colorectal cancer

Abstract: BackgroundInflammatory response markers are prognostic factors for several cancers, but their role in postoperative colorectal cancer (CRC) is unclear. The purpose was to evaluate the role of preoperative Neutrophil-to-Lymphocyte ratio (NLR), Platelet-to-Lymphocyte-ratio (PLR), and Lymphocyte-to-Monocyte ratio (LMR) in the prognosis of postoperative CRC patients.MethodsWe retrospectively reviewed 448 CRC patients who had undergone surgical resection from December 2015 to December 2017 in our hospital. The plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…To more accurately evaluate the impact of combined SII on survival time, we considered other potential factors that may affect survival time. By reviewing relevant literature ( 16 ), we identified the following 11 covariates: age, gender, postoperative adjuvant treatment, tumor location, tumor size, differentiation degree, presence of vascular and neural invasion, TNM stage, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9).…”
Section: Methodsmentioning
confidence: 99%
“…To more accurately evaluate the impact of combined SII on survival time, we considered other potential factors that may affect survival time. By reviewing relevant literature ( 16 ), we identified the following 11 covariates: age, gender, postoperative adjuvant treatment, tumor location, tumor size, differentiation degree, presence of vascular and neural invasion, TNM stage, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9).…”
Section: Methodsmentioning
confidence: 99%
“…Research evidence has shown significant associations between NLR, NMLR, PLR, SIRI, and SII and the prognosis of patients with cancer, and the parameters exhibited good predictive value. 10,35,36 MLR, PLR, and NLR are effective indicators for assessing CVD risk and predicting mortality. [37][38][39] Moreover, SIRI and SII are associated with the risk of acute coronary syndrome (ACS) in patients with chest pain.…”
Section: Dovepressmentioning
confidence: 99%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%